The Influence of Collaborative Leadership and Organization Based Self-Esteem on Work Engagement of Public Junior High School Teachers - Firda Desilia Amallilah; Masduki Ahmad; Rugaiyah (South Sulawesi Education Development (SSED), 2024)
Teachers are one of the most important human resources in education. Frequent curriculum changes, teachers' lack of understanding in running a digital-based education system, and the many administrative tasks that must be fulfilled make teachers rarely engage and contribute to the latest education system. This is due to the complexity of the teacher's role and the demands of a busy job. This study uses a quantitative approach with survey method and Structural Equation Modeling (SEM). The research data were obtained by questionnaire. The survey involved 148 teachers as samples. The sampling technique used simple random sampling. The results showed that (1) There is a direct effect of collaborative leadership on teacher work engagement with an Original Sample (O) value of 0.512 and P Values 0.000. (2) There is a direct effect of organizational based self esteem on teacher work engagement with an Original Sample (O) value of 0.206 and P Values 0.032. (3) There is a direct effect of collaborative leadership on organizational based self esteem with an Original Sample (O) value of 0.68 and P Values 0.000. (4) There is an indirect effect of collaborative leadership on teacher work engagement through organizational based self esteem with an Original Sample (O) value of 0.14 and P Values 0.038. The results of this study reinforce the urgency of the role of collaborative leadership and the importance of organizational based self esteem in improving teacher work engagement. The implications of this study highlight the importance of supporting teachers in facing changes and challenges and emphasize the need for leadership that motivates and builds teacher confidence.